Analisis Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Keputusan Pembelian dengan Kepuasan Pelanggan Sebagai Variabel Intervening: Studi Kasus Pada Pengguna Shopee di Kota Semarang - Rivaldo Saputro; Sukirman Sukirman; Nyoman Sri Padmini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the effects of service quality and product quality on customer satisfaction and purchase decisions, as well as the mediating role of customer satisfaction. The population consists of Shopee users in Semarang City (January–May 2025). Using the Lemeshow formula, 97 respondents were selected through purposive sampling. Data were collected using a 5-point Likert questionnaire and analyzed with SEM-AMOS. The findings show that both service quality and product quality significantly increase customer satisfaction. Service quality and product quality have positive but insignificant direct effects on purchase decisions, while customer satisfaction has a significant positive effect on purchase decisions. Customer satisfaction also significantly mediates the influence of service quality and product quality on purchase decisions. These results underline the crucial mediating role of satisfaction in shaping consumer purchasing behavior on digital platforms like Shopee.